Lens-specific expression of transforming growth factor beta1 in transgenic mice causes anterior subcapsular cataracts. - Srinivasan, Y (1998)
Transgenic mice were generated by microinjection of a construct containing a self-activating human TGF-beta1 cDNA driven by the lens-specific alphaA-crystallin promoter. Seven transgenic founder mice were generated, and four transgenic lines expressing TGF-beta1 were characterized. By postnatal day 21, mice from the four families exhibited anterior subcapsular cataracts. The lenses in these mice developed focal plaques of spindle-shaped cells that expressed alpha-smooth muscle actin, and that resembled the plaques seen in human anterior subcapsular cataracts. Transgenic mice showed additional ocular defects, including corneal opacification and structural changes in the iris and ciliary body. The corneal opacities were associated with increased exfoliation of the squamous layer of the corneal epithelium and increased DNA replication in the basal epithelium.